National Media Narrative Analysis In Reporting Related To The Discourse On Amendment Of The 1945 Constitution In Political Dynamics In Indonesia - Irwanto, Muhammad (Fakultas Hukum Universitas Gresik, 2022)
The emergence of issues and discourses on the Amendment of the 1945 Constitution, related to the recent extension of the President's term of office, has attracted serious attention from various elements of society in Indonesia, both for and against the discourses and opinions that have developed. This research is a qualitative research, by conducting an assessment of the models and narratives used by the national media in Indonesia, be it print media, electronic media, or television media. There are three discussions that are the focus of this research, namely the study and analysis of narratives in the national media coverage related to the extension of the presidential term, legal and political studies, to the implications in social dynamics on the issue of extending the presidential term. This research finds that national media narratives, such as the electronic media Tempo, Detik, Kompas, Tribune, JawaPos, have provided a description of information that is quite proportional in presenting various related sources that can interfere with concentration on more pressing problems in Indonesia today. . In the legal and political aspects, the Amendment certainly requires significant support from the DPR, the responses of several main parties that supported and supported President Joko widodo in the 2019 Presidential election, such as the Indonesian Democratic Party and the Indonesian Solidarity Party, showed that they did not provide an encouraging response for the support group. additional term of office of the President, although the response may change from time to time. In the social aspect of society, the issue of extending the term of the President, received a sufficient response in raising political tensions. Several important issues, such as the government's failure to stem the price of palm oil and the plan to increase the price of Pertamax fuel, are considered amid the issue of extending the term of office of the President.